2011
DOI: 10.1159/000324916
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid and Pentraxin-3 Levels Are Independently Associated with Coronary Artery Disease Risk in Patients with Stage 2 and 3 Kidney Disease

Abstract: Background and Objectives: Cardiovascular disease is prevalent in chronic kidney disease (CKD). Uric acid is increased in subjects with CKD and has been linked with cardiovascular mortality in this population. However, no study has evaluated the relationship of uric acid with angiographically proven coronary artery disease (CAD) in this population. We therefore investigated the link between serum uric acid (SUA) levels and (i) extent of CAD assessed by the Gensini score and (ii) inflammatory parameters, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 97 publications
1
27
1
Order By: Relevance
“…However, lack of correlation between arterial stiffness, as assessed by artery elasticity, and PTX3 levels in our cohort seems not consistent with previously reported associations between elevated PTX3 and surrogate markers of ED such as VCAM-1 [24], flow-mediated dilatation [21,33] as well as cardiovascular outcomes and severity of CAD in CKD patients [12,19,21].…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…However, lack of correlation between arterial stiffness, as assessed by artery elasticity, and PTX3 levels in our cohort seems not consistent with previously reported associations between elevated PTX3 and surrogate markers of ED such as VCAM-1 [24], flow-mediated dilatation [21,33] as well as cardiovascular outcomes and severity of CAD in CKD patients [12,19,21].…”
Section: Discussioncontrasting
confidence: 86%
“…Systemic inflammation is considered among the potential dysregulated pathways underlying CKDassociated ED [12]. CKD patients seem to be particularly prone to develop a state of persistent microinflammation, potentially due to raised production as well as decreased renal clearance of pro-inflammatory cytokines [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…These findings were also confirmed in meta-analyses 25,26 . Interestingly, similar results have been reported in patients with renal dysfunction [27][28][29][30] , thus highlighting the role of SUA as a possible CVD risk factor in these patients. Furthermore, hyperuricemia has been suggested as a risk factor for CKD development 31,32 and progression 33,34 .…”
Section: I a L D I S T R I B U T I O N U N A U T H O R I Z E D U S supporting
confidence: 83%
“…Therefore, the release of PTX3 may reflect vascular damage. Recently, several studies suggested that PTX3 might be associated with increased mortality in patients with vascular diseases [85]. A recent study in 376 patients with ischemic stroke showed that higher levels of PTX3 were independently associated with increased mortality in ischemic stroke patients [86].…”
Section: Inflammation-related Markermentioning
confidence: 99%